Life history of the river goby Glossogobius callidus (Teleostei: Gobiidae). Issue 6 (9th October 2020) - Mofu, Lubabalo; Woodford, Darragh J.; Wasserman, Ryan J.; Weyl, Olaf L. F.
Abstract: The river goby Glossogobius callidus is native to freshwater and estuarine habitats in South Africa. Individuals [21.1–144.4 mm total length ( L T )] were sampled from impoundments in the Sundays River Valley, Eastern Cape, from February 2014 to March 2015. The largest female was 137.2 mm L T, and the largest male was 144.4 mm L T . Length‐at‐50% maturity was 75.2 ± 2.1 mm L T for males and 76.2 ± 2.0 mm L T for females. Absolute fecundity was 1028.2 ± 131.7 oocytes per fish, and relative fecundity was 50.1 ± 18.1 oocytes per gram. The spawning season extended from October to December. Fish were aged using sectioned sagittal otoliths. The growth zone periodicity was validated using edge analysis. Longevity was more than 7 years for females and more than 6 years for males. Length‐at‐age was similar for the two sexes and was best described using the von Bertalanffy growth model as L t = 74.7(1 − e –1.0( t  + 0.1) ) mm L T for the entire population. Using the population age structure, the mortality rate was estimated at 1.3 per year.